Influence of Advertisement in Social Media Comedy Skits on Brand Awareness and Loyalty - Assumpta Munachimso Emelife (Mdooter Journal of Communication and Digital Technologies)
Objective: This study examined the influence of advertisements in social media comedy skits on brand awareness and loyalty.